Circular - Monks, Joe (1947)
035-0069-001 International Brigade Association SAM WILD (President I.B.A.) Commander British Battalion MALCOLM DUNBAR (Vice-President I.B.A.) Chief of Staff 15th Brigade JACK BRENT (Hon. Secretary I.B.A.) NAN GREEN (Secretary) 14 RED LION SQUARE, LONDON, W.C.1 Holborn 2583 HOLBORN BRANCH Flat 1, 20, Northington Street London, W.C.1. Dear Friend, The International Brigade Association remembers and appreciates the work done in the past by supporters of Spanish democracy in Holborn. You made Spain's cause your own and during the 52 months when Franco with the help of Hitler and Mussolini waged his cowardly war on the Spanish people's liberty, you collected money, food and medical supplies for the gallant Republican fighters who showed the world that it was possible to stand up to international Fascism. You took special pride in assisting the 2,000 British volunteers who gave military service in Spain. Therefore we ask you, now that Franco is the last Fascist Dictator with power in Europe, to return to the struggle to assist the unconquerable Spanish democrats who are striving to drive Franco from their country. If by our efforts we can influence our own Labour Government to recognise the exiled Spanish Republican Government and at the same time break off all trade and monetary agreements with Fascist Franco, when we will have fulfilled our sacred duty to the 540 of our British anti-Fascists who sleep in Spain. If you are still anxious to help in the cause of Spanish liberty, we ask you to attend and take part in a discission on how best we can in our way assist the Spanish democrats to liberate their land. We intend to have such a discussion at a meeting organised by the International Brigade Association in St. George the Martyr Hall, Old Gloster Street (Queen's Square), W.C.1. on Wednesday the 24th September at 7.30 p.m. We should be very grateful if you could attend. Yours sincerely, JOE MONKS Secretary, Holborn Branch I.B.A. 292/946/35/69